2012
DOI: 10.1029/2012ja017555
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of the coupled magnetosphere‐ionosphere‐thermosphere system on the Earth's magnetic dipole moment

Abstract: The strength of the Earth's magnetic field changes over time. We use simulations with the Coupled Magnetosphere‐Ionosphere‐Thermosphere model to investigate how the magnetosphere, upper atmosphere, and solar quiet (Sq) geomagnetic variation respond as the geomagnetic dipole moment M varies between 2⋅1022 and 10⋅1022 Am2. We find that the magnetopause stand‐off distance and the cross‐polar cap potential increase, while the polar cap size decreases, with increasing M. Their dependence on M is stronger than predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(98 citation statements)
references
References 35 publications
8
90
0
Order By: Relevance
“…Elias et al (2010) reported that a decrease of the magnetic field causes an increase in the Sq amplitude because of an enhancement in the ionospheric conductivities. Using the CMIT model, Cnossen et al (2012) confirmed that an increase in the ionospheric conductivities could generate long-term trends in the Sq amplitude of a similar order of magnitude to observed trends associated with a reduction in the dipole moment over the past century. Moreover, near the dip equator, the variations in the inclination of the magnetic field lead to a significant change in the Sq amplitude because the Cowling conductivity [Hirono 1952] is very sensitive to the inclination of the magnetic field.…”
Section: Introductionmentioning
confidence: 54%
“…Elias et al (2010) reported that a decrease of the magnetic field causes an increase in the Sq amplitude because of an enhancement in the ionospheric conductivities. Using the CMIT model, Cnossen et al (2012) confirmed that an increase in the ionospheric conductivities could generate long-term trends in the Sq amplitude of a similar order of magnitude to observed trends associated with a reduction in the dipole moment over the past century. Moreover, near the dip equator, the variations in the inclination of the magnetic field lead to a significant change in the Sq amplitude because the Cowling conductivity [Hirono 1952] is very sensitive to the inclination of the magnetic field.…”
Section: Introductionmentioning
confidence: 54%
“…The main aim of this work is to gain a better insight in the role of the dipole tilt angle in the MIT system and the mechanisms by which changes in tilt angle affect this system. This will help with understanding the effects of the more complex magnetic field changes that have occurred historically and complements two previous studies in which we examined the effects of changes in the dipole moment on the MIT system [ Cnossen et al , 2011, 2012]. A few simulations done with rather strong dipole tilts of 30°–60° are also interesting from a geological perspective, giving an idea of what the MIT system could be like during times of geomagnetic excursions, although in those cases the magnetic field is not necessarily dipolar.…”
Section: Introductionmentioning
confidence: 58%
“…These trends were attributed to solar extreme ultraviolet (EUV) radiation changes (Adler et al 1997;Yamazaki and Yumoto 2012), geomagnetic activity variations (Mikhailov and Marin 2001;Danilov 2002;Mikhailov 2001Mikhailov , 2006, the increase in greenhouse gas concentration (Bremer 1992(Bremer , 1998Upadhyay and Mahajan 1998;Ulich and Turunen 1997;Jarvis et al 1998), and/or secular variations of the Earth's main magnetic field (Foppiano et al 1999;Elias and Adler 2006;Elias 2009;Yue et al 2008;Richmond 2008, 2013;Cnossen et al 2012).…”
Section: Introductionmentioning
confidence: 99%